A self-assembling surface layer flattens the cytokinetic furrow to aid cell division in an archaeon - Sherman Foo; Ido Caspy; Alice Cezanne; Tanmay A. M. Bharat; Buzz Baum (Proceedings of the National Academy of Sciences, 2025)
The surface layer or “S-layer” is a two-dimensional lattice of proteins that coats a wide range of archaea and bacteria in place of a cell wall or capsular polysaccharides. S-layers are thought to play an important role in chemically and physically insulating cells from the external environment. Here, we show that the integrity of the S-layer in Sulfolobus acidocaldarius is maintained as cells grow via a process of self-assembly as SlaA monomers fill gaps in the lattice. Although this lattice which is physically tethered to the membrane might be expected to hinder cell division, we show that the S-layer flattens the membrane at cytokinesis to accelerate ESCRT-III-dependent cell division—and is important for robust, successful cell divisions under conditions of mechanical stress. Taken together, these results define the rules governing S-layer self-assembly and show how a flexible lattice coat that is coupled to the underlying membrane can both provide a cell with mechanical support and help to drive rapid and functionally important changes in cell shape.